Fully automated portal scraper - Stanišić Darko; Jorgovanović Nikola; Ilić Vojin; Koričić Dejan (Journal on Processing and Energy in Agriculture, 2011)
Portal scraper is machine widely used for bulk material supply of industrial facilities. Its performance is usually highly dependable on the ability of human operators since it relies on manual operation for some of its most sensitive functions. Fully automated portal scrapers with appropriate solutions for critical operation situations can significantly contribute to increasing the reliability of bulk material supply to the production process. Because of that, the analysis of portal scraper functionality and recognition of the main points of concern for its proper operation are presented in the paper as a base for the development of fully automated control solution. The time critical operations were identified and appropriate algorithms were developed for the reduction of time spent in unproductive motion.